Know your world social studies for pakistan 4 - Mansoob, Farhat (Oxford University Press; Karachi, 2014)
Know Your World: Social Studies for Pakistan by Farhat Mansoob is an informative textbook that covers the history, geography, and culture of Pakistan, designed to enhance students' understanding of their country and the world.